2008
DOI: 10.1158/0008-5472.can-08-0742
|View full text |Cite
|
Sign up to set email alerts
|

Focal Gains of VEGFA and Molecular Classification of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinomas represent the third leading cause of cancer-related deaths worldwide. The vast majority of cases arise in the context of chronic liver injury due to hepatitis B virus or hepatitis C virus infection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
700
2
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 617 publications
(759 citation statements)
references
References 51 publications
48
700
2
9
Order By: Relevance
“…A linear correlation was found between mRNA levels of VEGFA and extent of amplifi cation in human HCC ( 29 ). Amplifi cations in the VEGFA locus and juxtaposed regions were associated with advanced-stage HCC ( 30 ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A linear correlation was found between mRNA levels of VEGFA and extent of amplifi cation in human HCC ( 29 ). Amplifi cations in the VEGFA locus and juxtaposed regions were associated with advanced-stage HCC ( 30 ).…”
Section: Discussionmentioning
confidence: 89%
“…Amplifi cation of human Chr6p21 (the region syntenic for murine Chr17qB3) and whole chromosome gains were previously reported in several whole-genome analyses of human HCC with a frequency ranging between 7% and 40% (29)(30)(31)(32)(33). Accordingly, through FISH, we found VEGFA amplifi cations and chromosome 6 polysomies in 11% of human HCCs we tested (21 of 187; Fig.…”
Section: Locus Identifying a Molecularly Distinct Tumor Subpopulationmentioning
confidence: 88%
See 1 more Smart Citation
“…Hitherto, there are three large studies published that classify HCC based on gene expression. Two of them could identify subgroups with common affected pathways such as beta-catenin and proliferation signals [107,108] and one group [70,109] was able to correlate the subgroups with survival. Other studies tried to find common affected genes that are associated with prognostic factors such as vascular invasion and metastasis, but the overlap between these studies is very poor.…”
Section: Molecular Classificationmentioning
confidence: 99%
“…Multiple studies have revealed etiological patterns and multiple genes/pathways signifying initiation and progression of HCC. These pathways include CTNNB1/WNT‐β‐catenin, TPp53, ARID1/2s, HGF/c‐Met, and vascular endothelial growth factor/angiogenic signaling 5, 6, 7, 8, 9, 10, 11, 12. However, unlike the transforming growth factor β (TGF‐β) pathway, loss of p53 and/or activation of β‐catenin do not spontaneously drive HCC in animal models 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%